randFromArray("abkmnpvxy") randRangeNonZero( -20, 19 ) randRange( Y + 1, 20 ) Y < 0 ? "-" : "+" Y > 0 ? "-" : "+"

Solve for X:

X= Z - Y

\large{X + Y = Z}

Y > 0 ? "Subtract" : "Add" abs(Y) Y > 0 ? "from" : "to" both sides of the equation to get X by itself on the left.

\qquad\large{\begin{eqnarray} X &Y_SIGN abs(Y) &\quad=\quad& Z\\ &\pink{Y_SIGNINV abs(Y)} && \pink{Y_SIGNINVabs(Y)}\\ \end{eqnarray}}

\qquad\large{ X\gray{ + 0} \quad=\quadZ - Y }

Simplifying, X = Z - Y.

\large{Z = X + Y}

Y > 0 ? "Subtract" : "Add" abs(Y) Y > 0 ? "from" : "to" both sides of the equation to get X by itself on the right.

\qquad\large{\begin{eqnarray} Z &\quad=\quad& X &Y_SIGN abs(Y)\\ \pink{Y_SIGNINV abs(Y)} && & \pink{Y_SIGNINVabs(Y)}\\ \end{eqnarray}}

\qquad\large{ Z - Y \quad=\quad X\gray{ + 0} }

Simplifying, X = Z - Y.

\large{Y + X = Z}

Y > 0 ? "Subtract" : "Add" abs(Y) Y > 0 ? "from" : "to" both sides of the equation to get X by itself on the left.

\qquad\large{\begin{eqnarray} Y &+\enspace X &\quad=\quad& Z\\ \pink{Y_SIGNINV abs(Y)}& && \pink{Y_SIGNINVabs(Y)}\\ \end{eqnarray}}

\qquad\large{ \gray{0 + {}}X \quad=\quadZ - Y }

Simplifying, X = Z - Y.

\large{Z = Y + X}

Y > 0 ? "Subtract" : "Add" abs(Y) Y > 0 ? "from" : "to" both sides of the equation to get X by itself on the right.

\qquad\large{\begin{eqnarray} Z &\quad=\quad& Y + X\\ \pink{Y_SIGNINV abs(Y)} && \pink{Y_SIGNINVabs(Y)} \\ \end{eqnarray}}

\qquad\large{\begin{eqnarray} Z &\quad=\quad& Y + X\\ \pink{Y_SIGNINV abs(Y)} && \pink{\llap{Y_SIGNINV}abs(Y)} \\ \end{eqnarray}}

\qquad\large{ Z - Y \quad=\quad \gray{0 + }X }

Simplifying, X = Z - Y.